A practical guide to family proceedings : Blomfield and Brooks - Brooks, Helen, 1946-; Robinson, Richard (District judge); Simmonds, Christopher (District judge); Hickman, Neil; Thambyrajah, Joanne (London : Bloomsbury Publishing, 2022)
"Are you concerned about falling foul of the pitfalls across the spectrum of modern family proceedings? Established as a straightforward, easy-to-follow handbook of procedure, A Practical Guide to Family Proceedings: Blomfield and Brooks offers step-by-step guidance on the effective conduct of all the most common types of family law application. Fully revised and restructured in line with the changes resulting from the creation of the Family Court, the new Sixth Edition includes: -Coverage of the updated procedure for Presumption of Death applications - New chapters covering jurisdiction in children proceedings, public law for the private law practitioner, vulnerable witnesses and an introduction to appeals - Up to date with all recent amendments to the Family Procedure Rules Widely referred to within the Family Court, Principal Registry of the Family Division, other district registries and county courts, it is an essential reference work for family law practitioners whether as an aide-memoire for the hardpressed specialist or as an introduction for the less experienced"--
Chapter 1: The Divorce Petition -- Chapter 2: Requirements on Issue of Petition -- Chapter 3: Procedure - From Issue of Petition to Application for Decree Nisi -- Chapter 4: Answer and Subsequent Pleadings -- Chapter 5: Judicial Involvement Leading to Decree Nisi -- Chapter 6: Decree Absolute -- Chapter 7: Concluding Applications Other than by Decree or Final Order -- Chapter 8: Other Matrimonial Decrees -- Chapter 9: Declaratory Decrees -- Chapter 10: Civil Partnership -- Chapter 11: Applications for a Financial Order with Proceedings under the Matrimonial Causes Act 1973 and the Civil Partnership Act 2004 -- Chapter 12: Other Financial Applications -- Chapter 13: Children and Financial Applications -- Chapter 14: Financial Applications Governed by the Civil Procedure Rules 1998 -- Chapter 15: Procedures for the Enforcement of Financial and Costs Orders -- Chapter 16: Reciprocal Enforcement of Maintenance Orders -- Chapter 17: Jurisdiction in Child Proceedings -- Chapter 18: Children - Private Law Issues -- Chapter 19: Enforcement of Children Act Orders -- Chapter 20: Locating the Whereabouts of a Child -- Chapter 21: Wardship and Child Abduction -- Chapter 22: Public Law for the Private Law Practitioner -- Chapter 23: Family Homes and Domestic Violence -- Chapter 24: Emergency Applications -- Chapter 25: Penal Notices, Undertakings and Committal Applications -- Chapter 26: Court Bundles -- Chapter 27: Expert Witnesses in Family Proceedings -- Chapter 28: Vulnerable Witnesses in Family Proceedings -- Chapter 29: Appeals -- Chapter 30: The Court Record -- Appendix A: Precedents and Forms -- Appendix B: Blood and DNA Tests -- Appendix C: Other Information -- Appendix D: Rules and Supplementary Practice Directions -- Appendix E: European Regulations.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Keywords: Domestic relations -- England; Domestic relations -- Wales